“BİR TEREDDÜDÜN ROMANI”NDA POSTMODERN ROMAN UNSURLARI - Erdem, Nilüfer Aka (Fırat University, 2021)
Türk ve Batı edebiyatındaki edebi türlerin gelişimi üzerine kritikler ve incelemeler yapan Peyami Safa, romanda teknik konusunda farklılıklara ve yeniliklere açık bir anlayışa sahiptir. Roman türü konusunda teorisyen misali değerlendirmeleri olan yazar “mükemmel”e ulaşmak gayesiyle çeşitli teknikleri dener. Romanın ulusal ve uluslararası bağlamda geçirdiği dönüşümleri, aşamaları inceleyen Safa’nın Bir Tereddüdün Romanı adlı eserinde kurguyu şekillendiren teknikler ve karakterlerin konumu noktasında postmodern romana özgü nitelikleri kullandığı dikkat çeker. Modern ve postmodern anlayışın birbiri içinde yer aldığı bir dönemde kaleme alınan romanın modernden postmoderne geçişte kritik evreyi yansıtan bir geçiş dönemi ürünü olduğu söylenebilir. Romanda üst kurmaca, metinlerarasılık yönteminin ve çoğul bakış açısının kullanılması, yazar-okur-metin ilişkisinin roman yazma sürecine dâhil edilmesi, yazarın okuru metne dâhil ederek onunla konuşması ve roman içerisinde başka bir romanın yazılma sürecinin yer alarak ana metnin kurgusunu yönlendirmesi gibi teknikler postmodern romanın özellikleridir. Bu çalışmada, Bir Tereddüdün Romanı adlı eserin yapı ve içerik unsurlarının postmodern romanın özellikleriyle benzerliklerinin çözümlenmesi ve yorumlanması amaçlanmaktadır.

Peyami Safa, who carried out critiques and studies on the development of literary genres in Turkish and Western literature, had an approach that was open to differences and innovations in terms of technique in novels. The writer, who had theoretician-like comments on the novel genre, tried various techniques for the purpose of reaching “perfection”. It is seen that Peyami Safa examined the transformation and stages of the novel in the national and international contexts and used qualities unique to the postmodern novel at the point of techniques that shaped the construct and the positions of the characters in his work titled Bir Tereddüdün Romanı [the Novel of a Hesitation]. It may be argued that this novel that was written in a period where the modern and postmodern approaches were intertwined is a transition-period product that reflects a critical stage from the transition to the modern to the postmodern. In the novel, techniques like the use of metafiction, the method of intertextuality and a pluralistic point of view, the inclusion of the writer-reader-text relationship in the writing process, the writer’s inclusion of the reader into the text and his conversation with the reader and the fact that the writing process of another novel is included in the novel and directs the plot of the novel are characteristics of the postmodern novel. In this study, it is aimed to analyze and interpret the similarities of the structural and content-related elements of the work titled Bir Tereddüdün Romanı to the properties of the postmodern novel.
ELEMENTS OF THE POSTMODERN NOVEL IN “BİR TEREDDÜDÜN ROMANI”